Sacrifice and Stigma: Reducing Free-riding in Cults, Communes, and Other Collectives - Iannaccone, Laurence R. (Journal of Political Economy, 1992)
This paper presents an economic analysis of religious behavior that accounts for the continuing success of groups with strange requirements and seemingly inefficient prohibitions. The analysis does not presuppose any special motives for religious activity. Rather, religion is modeled as a club good that displays positive returns to "participatory crowding." The analysis demonstrates that efficient religions with perfectly rational members may benefit from stigma, self-sacrifice, and bizarre behavioral restrictions. The model also addresses sacrifice in nonreligious "social clubs": fraternities, communes, political parties, work groups, and families.